2000
DOI: 10.1097/00007890-200001150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunosuppression With Cyclosporine (Neoral) and SDZ Rad in Non-Human Primate Lung Transplantation: Systematic Pharmacokinetic-Based Trials to Improve Efficacy and Tolerability 1

Abstract: Combination of orally administered SDZ RAD and Neoral showed excellent immunosuppressive efficacy in a stringent lung transplant model. The drug interaction and the narrow therapeutic index of this drug combination required careful dose adjustments to optimize tolerability and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…35,36,62 Like sirolimus, RAD showed high efficacy in preventing and treating allograft rejections in rat models of heart, 46 kidney, 63 and lung transplantation [64][65][66] and in transplant models of nonhuman primates. [67][68][69] Most interesting were the results of studies investigating the effects of TOR inhibitors on chronic allograft diseases. Similar to the in vitro effects on mesenchymal cells, sirolimus was able to prevent and suppress intimal thickening in vascular grafts in small-animal models, 30,31 as well as in nonhuman primates: Although animals did not receive immunosuppressive therapy during the first 6 weeks after aorta transplantation between MLR-mismatched cynomolgus monkeys, sirolimus monotherapy started posttransplantation day 45 was able to halt and reverse graft vascular disease (Fig.…”
Section: Preclinical Animal Studiesmentioning
confidence: 99%
“…35,36,62 Like sirolimus, RAD showed high efficacy in preventing and treating allograft rejections in rat models of heart, 46 kidney, 63 and lung transplantation [64][65][66] and in transplant models of nonhuman primates. [67][68][69] Most interesting were the results of studies investigating the effects of TOR inhibitors on chronic allograft diseases. Similar to the in vitro effects on mesenchymal cells, sirolimus was able to prevent and suppress intimal thickening in vascular grafts in small-animal models, 30,31 as well as in nonhuman primates: Although animals did not receive immunosuppressive therapy during the first 6 weeks after aorta transplantation between MLR-mismatched cynomolgus monkeys, sirolimus monotherapy started posttransplantation day 45 was able to halt and reverse graft vascular disease (Fig.…”
Section: Preclinical Animal Studiesmentioning
confidence: 99%
“…These observations suggest that everolimus may be able to suppress the fibroproliferative processes and attenuate OB in human lung transplant recipients, in a manner analogous to the inhibition of myointimal proliferation and reduction of allograft vasculopathy in cardiac transplant recipients treated with an everolimus-containing regimen (13). A synergistic interaction between everolimus and CsA has been documented in experimental studies (14,15), and the combination has shown excellent immunosuppressive activity in lung transplant models (15)(16)(17) as well as in clinical trials in cardiac (13) and renal (18)(19)(20) transplant recipients. Everolimus possesses novel properties that may be able to target both acute and chronic rejection processes in lung transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The macrocyclic lactone everolimus (SDZ, RAD) RAD is a rapamycin derivative with potent immunosuppressive and antiproliferative properties. [6][7][8][9][10] It is further known to inhibit growth factor-driven cell proliferation of hematopoietic and nonhematopoietic cells. 6,10 In addition, RAD is a potent inhibitor of human Epstein-Barr virus (EBV)-transformed B lymphocytes in vitro and in vivo, arresting cell-cycle progression and increasing the apoptotic rate of EBV ϩ B cells.…”
Section: Introductionmentioning
confidence: 99%